State Downsizing and Its Impact on Development of Citizenship Education: Iran's Experience - Mojtaba Rajaei Khorasani; Mohammad Jalali; Saber Niyavarani (Comparative Education Society of Iran ( CESIR), 2021)
The realization of citizenship rights is inextricably linked to the functioning of both political and educational systems. The size of State has a direct effect and the function of education system has an indirect effect on realization of citizenship rights. The purpose of this study is to investigate the downsizing of State in education and its impact on development of citizenship education with emphasis on Iran's experience. Methods of research, data collection and data analysis were qualitative (textual analysis), documentary and qualitatively oriented respectively. Findings show that the role of State in the education sector with regard to citizenship rights can be adjusted based on two approaches of maximum and minimum intervention. Research findings also indicated the adoption of conflicting but supportive laws by legislatures for both approaches. Thus, on the one hand, the State does not want to reduce its involvement in education sector and on the other hand, wants to reduce its control in accordance with Article 44 of the Iran's Constitution. The consequence of this situation is the dominance of the maximum presence of the State in the education sector in favor of the "Right to Education" and the failure to minimize to the detriment of citizenship rights and diversity in its methods.